2014
DOI: 10.1021/nn502776h
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer MoS2 Heterojunction Solar Cells

Abstract: We realized photovoltaic operation in large-scale MoS2 monolayers by the formation of a type-II heterojunction with p-Si. The MoS2 monolayer introduces a built-in electric field near the interface between MoS2 and p-Si to help photogenerated carrier separation. Such a heterojunction photovoltaic device achieves a power conversion efficiency of 5.23%, which is the highest efficiency among all monolayer transition-metal dichalcogenide-based solar cells. The demonstrated results of monolayer MoS2/Si-based solar c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
705
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,154 publications
(723 citation statements)
references
References 31 publications
16
705
2
Order By: Relevance
“…1 Foreground ¼ 2D layered material (2DLM) stack þ background. 2 Transfer stack as originally specified by Dean et al: 22 PMMA 950 K, 4% (spin-on velocity 4000 rpm ! 290 nm) þ PVA 9 K, 4% (spin-on velocity 4000 rpm !…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Foreground ¼ 2D layered material (2DLM) stack þ background. 2 Transfer stack as originally specified by Dean et al: 22 PMMA 950 K, 4% (spin-on velocity 4000 rpm ! 290 nm) þ PVA 9 K, 4% (spin-on velocity 4000 rpm !…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] In addition to graphene, several other 2D layered materials, such as transition-metal dichalcogenides (TMDCs, also for use as channel materials) and hexagonal boron nitride (h-BN, as gate insulator), have been studied in detail. Due to the fact that 2D materials offer a large variety of different band gaps, heterostructures are particularly appealing since band-gap engineering becomes feasible while maintaining the ultrathin channel layer thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, monolayer or few‐layer MoS 2 can only absorb a small portion of incident light due to its ultrathin thickness, and its excellent optical absorption property cannot be well developed, thus restricting photocurrent (/photovoltage) improvement in MoS 2 ‐based devices. Therefore, recently, researchers have tried to prepare large‐scale uniform multilayer27 or bulk MoS 2 28 and have conceived a feasible and easy way to construct high‐performance optoelectronic devices by combining a 2D layered material with a traditional Si semiconductor,29, 30, 31, 32 as Si still dominates the commercial photovoltaic or optoelectronic market due to high abundance, acceptable power conversion efficiencies, and mature semiconductor technologies. Although the optical absorption can be improved greatly, the existing numerous defects result in serious recombination, and good PCEs still cannot be obtained 31, 32.…”
Section: Introductionmentioning
confidence: 99%
“…Modification of the bandgap and fabrication of large-scale defect-free films are important to achieve TMDC-based solar cell devices with decent efficiency. Recently reported heterojunction solar cells based on TMDC/graphene [163], TMDC/Si [164,165], TMDC/InP [166,167], graphene/Si [168,169] have shown excellent photovoltaic effect and power conversion efficiencies in the visible to infrared region. Solid-phase CVD is commonly used in the fabrication of these 2D semiconductor solar cells.…”
Section: Solar Cellmentioning
confidence: 99%
“…Solid-phase CVD is commonly used in the fabrication of these 2D semiconductor solar cells. Wang et al and Tsai et al demonstrated solid-phase precursors CVD-based monolayer MoS 2 /InP, MoS 2 /GaAs heterojunction and MoS 2 /p-Si solar cells, with PCE of 7.1%, 9.09%, and 5.23%, respectively [164,166]. Rehman et al reported a n-MoS 2 /p-Si solar cell fabricated by two-step process synthesis method, with 5.6% PCE.…”
Section: Solar Cellmentioning
confidence: 99%